Analysis of the diphtheria tox promoter by site-directed mutagenesis. - Boyd, J (1988)
By oligonucleotide-directed mutagenesis, we introduced alterations in the two putative -10 regions of the diphtheria tox promoter which are positioned at -50 and -56 from the GUG tox initiation signal. The -10 region positioned at -50 is favored in the expression of ADP-ribosyltransferase activity from the wild-type tox promoter in recombinant Escherichia coli; however, the promoter down mutation at position -50 is compensated for by increased activity of the -10 region positioned at -56.